Analisis Efektivitas Jalur Evakuasi Bencana Banjir - Samto Atmodjo, Pranoto; Sangkawati, Sri; Bayu Setiaji, Arief (MEDIA KOMUNIKASI TEKNIK SIPIL, 2015)
The flood disaster is one of the natural phenomena that are difficult to avoid. The risk of flood losses that occur in urban areas is generally greater than that occur in the countryside, which it is more due to the differences in the level of public welfare facilities and population density factors The increase in population and the high cost of residential land in urban areas, the greater the pressure of land use for settlement penetrated even in areas that have the potential to floodwaters. To avoid big losses due to flooding and loss of life, it is necessary to disaster management which includes the establishment of alternative evacuation routes, the storage location of refugee. This study will analyze and choose the path of evacuation of the population that are effective and safe as a result of flood-based Geographic Information System (GIS). Stages study began with an analysis of the magnitude of flooding, inundation extents, data collection and analysis of population, density and location of concentrations of residential quarters, global topography and the existing road network system. The study used a case in West Semarang Regency, with a fairly dense population and prone to flooding. Results of this study are expected to be applied to the area of research and can be used as a model for the evacuation of residents due to floods elsewhere.